Squamous cell lung carcinoma with gastrointestinal metastasis: a case report and review of literature - Li, Feifei; Liu, Yiqiang; Xu, Ke; Yao, Quan; Li, Qiang; Wu, Hong (Frontiers in Oncology, 2023)
Squamous cell lung carcinoma (LUSC) originates from squamous cells and has a high metastasis and recurrence rate. The lack of effective gene targets and specific treatment methods leads to poor prognoses for patients with LUSC. Gastrointestinal metastasis of LUSC is a rare occurrence in clinical practice. Patients with gastrointestinal metastasis usually have worse overall survival and a complex diagnosis and treatment compared to patients with metastasis elsewhere. Further, there are no helpful guidelines for treating patients with a clinically confirmed diagnosis of gastrointestinal metastasis. Here, we review the clinical features, diagnosis, and treatment of squamous cell lung carcinoma patients with gastrointestinal metastasis and report a rare case of squamous cell lung carcinoma accompanied by gastrointestinal metastasis. Our learnings from the case demonstrate the poor prognosis of squamous lung cancer metastasizing to secondary lymphoid organs of the gastrointestinal tract. Therefore, surgical resection is recommended to prolong the survival of patients with squamous cell carcinoma of the lung who develop gastrointestinal metastases.